Potensi Antimikroba Ekstrak Etanol Kulit Luar Buah Cempedak (Artocarpus integer (Thunb.) Merr.) - Rina Saputri; Ali Rakhman Hakim; Dahlia Syahrina; Fatthiya Lisyanti (Jurnal Surya Medika (JSM), 2019)
The background of this research is to develop the potential of biological resources in South Kalimantan. In particular, the biological source is cempedak fruit. The use of cempedak which has been scientifically studied is the use of cempedak bark as anti-malaria. Other studies related to other parts of cempedak are still not widely used. Based on the potential possessed by cempedak bark, it is likely that other parts of cempedak also have potential as traditional medicine. This study aims to identify the content of secondary metabolites from the outer skin of cempedak fruit, analyze the potential of the outer skin of cempedak fruit as an antimicrobial and analyze the effective dose as an antimicrobial. The method used to see MIC values with liquid dilution and KBM values with solid dilution. The results of phytochemical identification showed that the ethanol extract of the outer skin of cempedak fruit contained secondary metabolites in the form of saponins, tannins, flavonoids and alkaloids which have antimicrobial potential. The results of the antimicrobial activity test showed the MIC value of the ethanol extract of cempedak fruit outer skin against Escherichia coli bacteria at a concentration of 50% and against Staphylococcus aureus at a concentration of 25%. The KBM value also shows the same value as KHM. Based on the results of the study it can be concluded that the ethanol extract of cempedak fruit outer skin has broad-spectrum antimicrobial activity.